Lives of circumcised and veiled women: a global-Indian interplay of discourses and narratives - Chatterjee, Debangana (Routledge, 2024)
Introduction : women's bodies and the politics of representation -- Pain, perception and FC/FGC : international discourses on rights and representation -- Khafz in India : culture, narratives and counter-narratives -- Veiling in international arena : a fractured discourse -- Local discourses on veiling in India : narratives from the field.